Effect of post-partum breeding interval on conception rates in beef cows - G.H. Kiracofe; Kenneth G. Odde (Kansas Agricultural Experiment Station Research Reports, 1978)
We analyzed date on 1536 fall calving Angus cows to determine the effect of post-partum breeding interval on conception rates in beef cows. Normal fertility was observed for cows showing heat 40 or more days post-partum.
Keywords: Cattlemen& #x27; s Day; 1978; Report of progress (Kansas State University. Agricultural Experiment Station); 320; Beef; Post-partum breeding; Conception rates